Game Theory Applications in Cybersecurity: An Operations Research Approach - S. Tanak, Khader (Journal of Al-Qadisiyah for Computer Science and Mathematics, 2025)
Modern cybersecurity challenges require dynamic defense mechanisms able to waiting for antagonistic strategies at the same time as balancing operational constraints. This study unifies recreation theory and operations studies (OR) to create an adaptive framework for countering sophisticated cyber threats, empirically tested the use of the QRID-2025-Dataset-Small.Csv. By synthesizing Stackelberg games (modeling hierarchical attacker-defender interactions), evolutionary video games (taking pictures long-term antagonistic evolution), and signaling games (addressing deception) with OR methods—including blended-integer programming and Markov choice processes—the framework optimizes useful resource allocation and selection-making beneath uncertainty. Empirical results spotlight a 65.7% discount in superior chronic danger (APT) breaches and a three.41 go back on investment (ROI) for ransomware mitigation, surpassing rule-based totally and machine mastering benchmarks. The technique achieves linear scalability ((O(n))) and adapts to heterogeneous environments, inclusive of high-noise situations (30% of instances), overcoming barriers of static or fragmented solutions. The take a look at contributes a pioneering integration of game-theoretic equilibrium evaluation with stochastic OR optimization, proven towards real-global value metrics (CostTime, CostMoney, CostEnergy) derived from 500 assault simulations. Practical programs are demonstrated in time-touchy sectors like healthcare and commercial manage structures (SCADA), where fee-effective speedy response is critical. By merging strategic adversary modeling with operational efficiency, this work advocates for future improvements in AI-driven actual-time threat prediction and behavioral technological know-how to beautify human-centric protection strategies. The framework gives a scalable, replicable model for protecting essential infrastructure in opposition to escalating cyber risks, urging cross-disciplinary collaboration between academia and enterprise.